Measuring and Analyzing the Impact on Fiscal Policy Instruments on Inflation in Iraq 2004-2020 - Al-Dosky, Khalil; Hassan, Mohsen; Mohammed Amin, Mohammed Amin (Humanities Journal of University of Zakho, 2021)
Inflation is one of the most important indicators of economic instability and its high rates have negative effects on the standard of living of individuals and the investment environment for projects that require the development of appropriate solutions and intervention with the available means, and this research is an attempt to estimate and analyze the impact of some financial policy tools on inflation in Iraq for the period 2004-2020, and assuming that these tools have A significant effect on inflation, a standard model based on economic logic has been formulated to estimate, test and analyze the short and long-term relationships between the variables involved in it. It was found that these variables have different effects in the short and long term and that two out of three of them do not have a significant effect in the long term. This pushes the suggestion to adopt these tools in the short term. In the long term, economic policies should be formulated based on other tools, which may be monetary among them.